1979
DOI: 10.1099/00221287-110-1-211
|View full text |Cite
|
Sign up to set email alerts
|

Protein II* Influences Ferrichrome-iron Transport in Escherichia coli k12

Abstract: Ferrichrome-promoted iron uptake in Escherichiu coli ~1 2 is strictly dependent upon the tonA gene product, a 'minor' outer membrane protein. By selection for mutants of E. coIi resistant to phages which require 'major' outer membrane proteins as receptors, strains with pronounced protein deficiencies were constructed. Such strains were tested for anomalous behaviour of ferrichrome transport. No significant differences in iron uptake were detected in E. coli K12 strains with markedly reduced amounts of protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1980
1980
1999
1999

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…1). These alterations revised the FeEnt uptake K m to lower values, and comparable binding studies similarly reduced the adsorption K d , suggesting that previous methodologies for the measurement of these parameters (Coulton and Braun, 1979;Ecker et al, 1986;Newton et al, 1997;Thulasiraman et al, 1998) were subject to substrate depletion artifacts, and therefore inaccurate. These experiments also indicated that it was necessary to customize the transport conditions individually for FepA mutants that manifest either lower affinity or lower transport efficiency.…”
Section: Siderophore Nutrition Testsmentioning
confidence: 85%
See 2 more Smart Citations
“…1). These alterations revised the FeEnt uptake K m to lower values, and comparable binding studies similarly reduced the adsorption K d , suggesting that previous methodologies for the measurement of these parameters (Coulton and Braun, 1979;Ecker et al, 1986;Newton et al, 1997;Thulasiraman et al, 1998) were subject to substrate depletion artifacts, and therefore inaccurate. These experiments also indicated that it was necessary to customize the transport conditions individually for FepA mutants that manifest either lower affinity or lower transport efficiency.…”
Section: Siderophore Nutrition Testsmentioning
confidence: 85%
“…Both the binding and transport of ferric siderophores by ligand-gated porins were characterized as multicomponent or co-operative processes (Coulton and Braun, 1979;Locher and Rosenbusch, 1997;Thulasiraman et al, 1998), but the revision of our methodologies essentially eliminated the allostery that occurs during FeEnt binding and uptake in vivo (Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transport of 5Fe3+-ferrichrome. Cells to be tested for the uptake of 55Fe3" from the ferrichrome-iron complex (12) were grown in M9 minimal medium, washed twice with iron uptake medium (10 mM Trishydrochloride, pH 7.2, 0.5% glucose, 1.0 mM MgSO4), and resuspended in iron uptake medium plus 100 ,uM nitrilotriacetate to an absorbance at 578 nm of 0.40, corresponding to 0.38 mg (dry weight)/ml. Bacteria were equilibrated at 37°C for S min, and uptake of (17).…”
Section: Dna Gel Electrophoresis Electrophoresis Of Dnamentioning
confidence: 99%
“…E. coli K-12 strains PL-6 (aroB thi r cir feuB TuII* r [9]), MC4100 [F-araD ⌬(argF-lac)U169 rspL thi relA flbB deoC pstF rbsR (40)], SG303 (MC4100 aroB [7]), and AW740 (hisG4 thr-1 fhuA31 tsx-78 ⌬ompF zcb::Tn10 ⌬ompC [20]) were used as hosts for protein expression. E. coli CS2529 (F Ϫ thr leuB6 proA argE his thi galK lacY1 trpE non mtl xyl ara-14 rfaK2::⍀Km r [27]) expresses truncated lipopolysaccharide (LPS) and was used to enhance recognition of FhuA on intact cells by MAbs.…”
Section: Methodsmentioning
confidence: 99%